The Relationship of Entrepreneurship Education and Entrepreneurial Motivation to Entrepreneurial Innovation Through Entrepreneurial Mindset as an Intervening Variable Mindset as an Intervening Variable in Vocational School Students in Mojokerto - Fitriah, Akha Anis; Wardana, Ludi Wishnu; Kusdiyanti, Heny (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to investigate the impact of entrepreneurship education and entrepreneurship promotion on new entrepreneurship through entrepreneurship among students working at Mojokerto. The sampling method used is a sampling method that uses the Slovin sample with a sample size of 225. The data analysis method used in this study is SEM-PLS (Structural Equation Modeling-Partial Least Square) using the Smart PLS version 3 software. This study uses two PLS calculation models: the external model) and the ( Inner Model). Model). According to the results of this study, business education was found to be beneficial to business innovation, business promotion has a positive effect on business development, and business education is helpful to business thinking. has a positive (+) impact on the market. Entrepreneurial spirit has been shown to promote entrepreneurial innovation through entrepreneurial education and entrepreneurial empowerment.